Post-War Justice - Ohlin, Jens David (DIXI, 2016)
When hostilities reach a conclusion —whether or not they were part of a formal armed conflct—, the parties must be held accountable for their actions. The belief is almost universally held, regardless of one’s moral or ethical convictions. However, the details of this responsibility are highly controversial and disputed. In the second section of this short article, a legal basis for post-war justice is provided that appeals to the anti-impunity norm. It is then concluded that criminal proceedings uphold the anti-impunity norm better than non-criminal mechanisms. In light of this conclusion, the third section poses the following questions:How do we achieve post-war justice? Who should be brought to trial: leaders or soldiers? Should they be tried in national or international courts? What should they be charged with: national or international crimes? What procedures should be followed in the trials and how? Finally, why should they be punished?